Developing an interactive 360Â° virtual tour website to enhance the environment guiding tour in a building - Tan, Yen Xin (2022)

(untitled)
This project describes the development of virtual tour website project for displaying the Vista Kinderworld, a kindergarten located in Kuala Lumpur. The virtual tour allows users to explore the different places of the kindergarten such as classroom, swimming pool, canteen and playground, through controlling the interactive navigation buttons. Navigating from one place to another is convenient and time-saving with the help of highlight reel that display various spots in the building. The users are also able to gain information about the places from the pop-up information dialogues initiated by the mouse clicked event. In addition, the virtual tour is equipped with the background music and the audio narrator that is triggered by the arrival of the users at certain spots in the building. It helps users in better understanding each place in the building by storytelling, which additionally creates a more immersive and realistic user experience while taking the virtual tour.